Hubungan Personal Hygiene dengan Kejadian Penyakit Kulit Scabies - Nurohmah, Nurohmah; Daeli, Weslei (Journal of Nursing Education and Practice, 2024)
Introduction: Scabies is a disease caused by Sarcoptes Scabiei Var Hominis, whose transmission occurs by direct or indirect contact, with symptoms that can be felt such as excessive itching, often appearing at night, bumps and rash spots like blisters caused by scratching. Objectives: To see the relationship between personal hygiene and the incidence of scabies coolie disease at the Al-Qur'an Islamic Boarding School Attasdiq, Sukamaju Baru Village, Tapos District, Depok City in 2022. Method: This research is a quantitative analytic descriptive research. The research design approach used was the Cross-Sectional approach. The sample used in this study was the children of the Al-Qur'an Islamic boarding school Attasdiq, Sukamaju Baru Village, Tapos District, Depok City, with as many as 30 people experiencing scabies. Data was collected using the Pratiwi Modification Questionnaire with factors according to (Florence Nightingale in 2018) taken from the journal library Airlangga University and the Scabies Modification Questionnaire was taken (PJB Primary Data 2019) taken from the journal Appendix 3. Data analysis was carried out in the form of a print-out questionnaire in percentage form using statistical techniques Chi-square Test and Normality Test. Result: The research results show a relationship between personal hygiene and the incidence of scabies skin disease with a P-value of 0.000 (P-value > 0.05). Conclusion: There is a relationship between personal hygiene and the incidence of scabies skin disease at the Al-Qur'an Attasdiq Islamic Boarding School, Sukamaju Baru Village, Tapos District, Depok City.